Research on policy effect and regional difference of allocation efficiency of rural preschool education resources: evidence from China - Miao miao Tang; Qiang Lan (PLoS ONE, 2025)
By the end of 2020, with all rural residents living in poverty under the current standard lifted out of absolute poverty, marking a new phase in China’s anti-poverty efforts with new pursuit of the consolidation and expansion of poverty alleviation achievements in the effective connection with rural revitalization. The development and improvement of funding mechanisms for rural preschool education are crucially important to further promoting rural development. Employing an input-oriented three-stage DEA model and the Malmquist index, this study conducts a static and dynamic analysis of resource allocation performance in rural preschool education across 30 provinces in China (excluding Tibet, Hong Kong, Macao, and Taiwan). The findings reveal that random factors and environmental variables lead to an underestimation of rural preschool education investment performance. Secondly, economically developed regions are not necessarily equipped with higher performance in rural preschool education investment as regional differences stem from the combined effects of various economic, agglomeration, demographic, and scale factors across different areas of the country. Finally, based on these empirical results, this paper proposes policy recommendations to enhance resource allocation performance in China’s rural preschool education.